Synthetic Routes to 2-Iminothiazolidines: State-of-the-Art 2006-2020 - Bhattacharyya, Aditya (Current Organic Chemistry, 2020)
Multiheteroatom-containing small-sized cyclic molecules such as 2- iminothiazolidines are often found to possess beneficial pharmacological properties. In this review article, the biological significance of 2-iminothiazolidines is discussed and the literature reports published in the last 15 years spanning from 2006 to 2020 describing various preparative routes to access 2-iminothiazolidine derivatives have been categorically and chronologically described. The notable synthetic methods discussed here involve ringexpansion transformations of nonactivated and activated aziridines, thiiranes, epoxides, and other miscellaneous reactions.
Keywords: thiirane